Positive parenting and adolescent prosocial behaviour – a mediation analysis with representative data - Heidi Backman; Katri Lahti; Taina Laajasalo; Markus Kaakinen; Eeva T. Aronen (International Journal of Adolescence and Youth)
Understanding factors promoting adolescent prosocial behaviour is crucial for positive development. This study explores how positive parenting relates to prosocial behaviour. Utilizing data from a nationally representative sample of 5,317 Finnish adolescents (mean age 15.2, 51.3% girls), we examined the mediating roles of self-control, identification with family and friends, and the moderating effects of gender and antisocial peers. The results revealed that both parental warmth and monitoring were positively associated with prosocial behaviour. Self-control, identification with family and friends, and gender significantly influenced this relationship. Boys appeared more receptive to the positive influence of parenting, while the presence of antisocial peers weakened the link between parental warmth and prosociality. Furthermore, identification with family and friends strengthened the positive effects of parenting on prosocial behaviour. These findings underscore the complex interplay of individual and social factors, highlighting their roles in shaping adolescent prosocial development.